2011
DOI: 10.1007/s00262-011-0998-2
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide short-circuits interleukin-12-mediated tumor regression

Abstract: Interleukin-12 (IL-12) can promote tumor regression via activation of multiple lymphocytic and myelocytic eVectors. Whereas the cytotoxic mechanisms employed by T/NK/NKT cells in IL-12-mediated tumor kill are well deWned, the antitumor role of macrophage-produced cytotoxic metabolites has been more controversial. To this end, we investigated the speciWc role of nitric oxide (NO), a major macrophage eVector molecule, in post-IL-12 tumor regression. Analysis of tumors following a single intratumoral injection of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…Induction of IL-10 (3), inducible NO synthase (4), and, more recently, regulatory T cell (Treg) expansion (5) have been identified as potential mechanisms that limit the duration of IL-12-driven cytotoxic T cell activity. Whereas production of IL-10 and inducible NO synthase are rapid but transient events (6,7), post-IL-12 Treg rebound is progressive and long-lasting (5). Recent work revealed that IFN-g, which is essential to the antitumor activity of IL-12, also induced IDO + dendritic cells (DC) in the tumor and the tumor-draining lymph node (TDLN), and that IDO + DC orchestrated the post-IL-12 Treg expansion (8).…”
mentioning
confidence: 99%
“…Induction of IL-10 (3), inducible NO synthase (4), and, more recently, regulatory T cell (Treg) expansion (5) have been identified as potential mechanisms that limit the duration of IL-12-driven cytotoxic T cell activity. Whereas production of IL-10 and inducible NO synthase are rapid but transient events (6,7), post-IL-12 Treg rebound is progressive and long-lasting (5). Recent work revealed that IFN-g, which is essential to the antitumor activity of IL-12, also induced IDO + dendritic cells (DC) in the tumor and the tumor-draining lymph node (TDLN), and that IDO + DC orchestrated the post-IL-12 Treg expansion (8).…”
mentioning
confidence: 99%
“…Also, NO is a major macrophage effector molecule stimulated to be released under inflammatory conditions. Macrophage NO can be cytotoxic to tumor cells; however, NO produced by the infiltrating macrophage can also be cytotoxic to anti-tumor lymphocytes [72]. Immune inhibition by iNOS was found to be stronger than tumor cell cytotoxic effector functions; therefore macrophage NO had dramatic negative effects on the survival of anti-tumor CD8+ T cells in a murine tumor model.…”
Section: C5a Enhancement Of Recruitment and Anti-tumor Effects On Macmentioning
confidence: 99%
“…TNF-a release may be restricted for extended amounts of time [72]. NO is a lipophilic molecule and easily migrates across cell membranes to act intracellularly, and signaling and post-translational modifications lead to anti-apoptosis and increased cell growth of recipient cells [72]. NO is a shortlived molecule; however, iNOS can induce sustained levels of NO, expanding the duration and levels of NO in the environment [57].…”
Section: C5a Enhancement Of Recruitment and Anti-tumor Effects On Macmentioning
confidence: 99%
See 2 more Smart Citations